Importin α3 (KPNA3) Deficiency Augments Effortful Reward-Seeking Behavior in Mice - Aomine, Yoshiatsu; Sakurai, Koki; Macpherson, Tom; Ozawa, Takaaki; Miyamoto, Yoichi; Yoneda, Yoshihiro; Oka, Masahiro; Hikida, Takatoshi (Frontiers in Neuroscience, 2022)
Importin α3 (Gene: Kpna3 in mice, ortholog of human Importin α4) is a member of the importin α family and participates in nucleocytoplasmic transport by forming trimeric complexes between cargo proteins and importin β1. Evidence from human studies has indicated that single nucleotide polymorphisms (SNP) in the KPNA3 gene are associated with the occurrence of several psychiatric disorders accompanied by abnormal reward-related behavior, including schizophrenia, major depression, and substance addiction. However, the precise roles of importin α3 in controlling reward processing and motivation are still unclear. In this study, we evaluated the behavioral effects of Kpna3 knockout (KO) in mice on performance in touchscreen operant chamber-based tasks evaluating simple (fixed-ratio) and effortful (progressive-ratio) reward-seeking behaviors. While Kpna3 KO mice showed no significant differences in operant reward learning on a fixed-ratio schedule, they demonstrated significantly increased motivation (increased break point) to instrumentally respond for sucrose on a progressive-ratio schedule. We additionally measured the number of c-Fos-positive cells, a marker of neural activity, in 20 regions of the brain and identified a network of brain regions based on their interregional correlation coefficients. Network and graph-theoretic analyses suggested that Kpna3 deficiency enhanced overall interregional functional connectivity. These findings suggest the importance of Kpna3 in motivational control and indicate that Kpna3 KO mice may be an attractive line for modeling motivational abnormalities associated with several psychiatric disorders.